Hepatitis A virus-associated fulminant hepatitis with human immunodeficiency virus coinfection. Issue 2 (February 2020) - Maki, Yohei; Kimizuka, Yoshifumi; Sasaki, Hisashi; Yamamoto, Takayuki; Hamakawa, Yusuke; Tagami, Yoichi; Miyata, Jun; Hayashi, Nobuyoshi; Fujikura, Yuji; Kawana, Akihiko
Abstract: Hepatitis A virus (HAV) commonly causes acute hepatitis in humans and is transmitted through the fecal-oral route or by ingestion of contaminated food or water. HAV infection generally follows a self-limiting course; it can seldom cause fulminant hepatitis that increases the risk of mortality. To the best of our knowledge, this is the first reported fatal case of fulminant hepatitis caused by HAV in a 40-year-old male with human immunodeficiency virus (HIV) infection. The HAV genotype in this case was IA, which has recently become common globally among people living with HIV (PLWHIV), intravenous drug users, and homeless people especially in developed countries. His HIV infection was stabilized by antiretroviral drugs and his CD4 values were stable. He developed acute hepatic encephalopathy, did not respond to repeated plasma exchange therapy, and died rapidly. It is known that HIV co-infection sometimes leads to fulminant non-HAV hepatitis, although evidence supporting a correlation between fulminant hepatitis A risk and HIV infection is still lacking. This case demonstrated the fatal risk of HAV infection in PLWHIV; it was suggested that education about appropriate preventive measures and vaccination are important for preventing HAV infections among PLWHIV.